Phenotypic Switches Induce Fractal Morphology of Bacillus subtilis Biofilm - Jin Li; Jin Wu; Jiahao Cui; Jiankun Wang; Xiaoling Wang (Environmental Microbiology, 2025)
The height profile of Bacillus subtilis biofilms exhibits complex fractal morphology shaped by cellular behaviour and environmental factors. While phenotypic differentiation relates to biofilm spatial patterns, the mechanisms regulating upper surface morphology remain unclear. This study combines experiments with an agent‐based model to explore how nutrient‐driven phenotypic switches affect the morphological complexity (fractal dimension D ) and heterogeneity (roughness Ra) of the biofilm upper surface. We analyse biofilm images at different nutrient concentrations to quantify morphology. The model incorporates Monod kinetics, with phenotypic transition probabilities and mechanical interactions depending on substrate availability. The results show that nutrient conditions regulate phenotypic ratios, and matrix‐producing cells promote anisotropic biofilm growth, enhancing surface heterogeneity and morphological complexity. Spores fill vacancies created by heterogeneous cell growth, and this behaviour, in coordination with isotropic growth of motile cells, reduces the morphological complexity and heterogeneity of biofilm morphology. When the populations of matrix‐producing cells and the other two phenotypes balance, the biofilm's morphological complexity and heterogeneity peak. The model accurately predicts experimental trends, revealing that phenotypic transitions mediated by metabolic dependence and nutrient diffusion drive biofilm morphogenesis. This work links cell differentiation to biofilm upper surface morphology, advancing our understanding of biofilm adaptation in dynamic environments.